Advanced Carcinoma Endometrium in a Reproductive Age Group Woman: A Magnetic Resonance Imaging Diagnosis - Fatma Mohamed Al Wahaibi; Raya Salim Al Busaidi; Yasser Mahfouz; Vaidyanathan Gowri; Ajit Sebastian (Dubai Medical Journal)
Introduction: Endometrial adenocarcinoma, usually seen in postmenopausal women, can also occur in younger patients and is often associated with polycystic ovarian syndrome (PCOS) and obesity.